Drug-induced rhinitis as a complication of using mucosal decongestants - Kalinowska, Zuzanna; Matera, Weronika; Krężel, Maciej; Snoch, Olga (Journal of Education, Health and Sport, 2025)
Rhinitis medicamentosa is induced by the overuse of topical nasal decongestants. It is characterized by chronic nasal obstruction, not related to allergy or common cold. This problem often affects young and middle-aged patients who, in order to reduce nasal congestion, exudation and swelling of the nasal mucosa, use drugs that only initially relieve the patient's symptoms. Rhinitis medicamentosa is associated with the risk of many complications, including the development of nasal polyps, otitis and sinusitis. The basis of treatment is discontinuation of decongestants and the use of nasal corticosteroid. In situations where conservative treatment is not sufficient, surgical methods can also be used. It is complicated to cure and the therapy is often long-lasting. Therefore, it seems much easier to prevent the development of rhinitis medicamentosa by avoiding this type of drugs or using nasal decongestant only for short periods and in correct doses.